2011
DOI: 10.1111/j.1753-0237.2011.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil price shocks and the dynamics of current account balances in Nigeria

Abstract: This paper pioneers research on the relationship between oil price shocks and current account dynamics in Nigeria, a country that doubles as an oil exporter and importer. Structural vector autoregression is applied to quarterly data from 1970Q1 to 2008Q4 to identify oil price shocks and to evaluate its net effect on Nigeria's current account balances. After introducing three control variables (output gap, real exchange rate misalignment and the lagged values of current account ratio), we impose six structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…In either case the trade balance of the economy would deteriorate. The result obtained is consistent with results obtained by Chuku et al (2011) and Kilian et al (2009).…”
Section: Journal Of Economic and Financial Studies (Jefs)supporting
confidence: 93%
See 3 more Smart Citations
“…In either case the trade balance of the economy would deteriorate. The result obtained is consistent with results obtained by Chuku et al (2011) and Kilian et al (2009).…”
Section: Journal Of Economic and Financial Studies (Jefs)supporting
confidence: 93%
“…Unlike Chuku et al (2011) and Kilian et al (2009), Mucuk, Gerçeker andAy (2013) focused on the effect of fluctuations in the price of oil on current account balance of Turkey and found that increases in the price of crude oil resulted in current account deficit. However, their study did not take into account the role of the source of the oil price shock which per the argument of Kilian et al (2009) andChuku et al (2011) could have influence on how oil prices would affect the current account balance.…”
Section: Journal Of Economic and Financial Studies (Jefs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in oil revenues was found to have a positive impact on Kuwait's government consumption expenditure, money supply and the consumer price index (Eltony and Al‐Awadi, ). Oil prices also played a significant impact on Nigeria's output, real exchange rate and the current account (Chuku et al ., ). However, different results were arrived at by Adeniyi et al .…”
Section: Introductionmentioning
confidence: 97%